Implementasi Pembelajaran Berdiferensiasi di SMP Bangkinang - Hela Azzahra (Jurnal Pustaka Cendekia Hukum dan Ilmu Sosial, 2024)
This study aims to determine the implementation of differentiated learning in mathematics subjects at one of the junior high schools in Bangkinang. This research is a qualitative research with a case study approach. The data analysis technique used is triangulation technique that confirms the data obtained based on observation and documentation. The research shows that teachers have successfully implemented differentiated learning in the classroom. Teachers have implemented process differentiation and product differentiation in the learning process. The results of this differentiated learning have a positive impact on students and educators. Through differentiated learning in the independent curriculum, the learning process succeeds in providing learners' rights so that learners can express their characteristics based on their interests and potential.